Application of Green Economy in Malini Agro Park - Suartana, I Wayan; Suryanawa, I Ketut (Journal of A Sustainable Global South; Vol 4 No 2 (2020): August 2020DO - 10.24843/jsgs.2020.v04.i02.p04, 2020)
Development that exploits natural resources is an easy story to hear. The exploitation-based development model that is maintained will only result in marginalization. A green economy as a means of achieving sustainable development is designed to protect and increase the value of the natural resource base, increase resource efficiency, promote sustainable or environmentally friendly patterns of production and consumption, and encourage the world towards low carbon development. Green economy policies and measures should be designed to improve the integration between economic development and its sustainable aspects. A development that combines economic, social and environmental interests to meet the needs of the current generation without sacrificing the interests of future generations. For this reason, Malini Agro Park, which is located in the arid area of ??Pecatu, implements an integrated hydroponic system to support sustainable development. The specific objective of this research is to examine in depth the implementation of green accounting at Malini Agro Park. Index Terms — green economy, triple bottom line accounting